PENGEMBANGAN KURVA DISTRIBUSI HUJAN SINTETIS DI KOTA BEKASI, JAWA BARAT - Ginting, Segel (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
The rainfall time distribution has a significant influence in determining the peak magnitude and the volume of runoff as well. Generally, rainfall-based runoff predictions require a rainfall-time distribution, and are usually met using patterns generated from other areas, thus giving inaccurate results. For this reason, time distribution of rainfall pattern is needed in accordance with local and specific conditions, especially in Bekasi City. This study aims to develop a synthetic rainfall time distribution pattern in Bekasi City, so that it can assist planners in designing appropriate drainage channel dimensions. Various types of rain data are needed for this study. Short duration of rainfall data with a recording interval of 5 minutes from 2010 to 2020 at the Bekasi rainfall station were collected. The data is processed into rain data for 5 minutes, 10 minutes, 15 minutes, 30 minutes, 1 hour to 3 hours. The method used is frequency analysis of historical data by forming a graph that connects the percentage of rainfall accumulation with the percentage of rainfall duration. As a result, a rainfall time distribution pattern has been formed in Bekasi City for a duration of 60 minutes to 180 minutes. The produced synthetic rainfall time distribution pattern has an early peak shape and is different from the distribution pattern that has been widely used such as the Mononobe method, the Chicago method, the SCS method and the Huff method.Keywords: Hyetograph rainfall, time distribution of rainfall, urban drainage, intensity duration frequency